Peran ekstrakurikuler seni tari dalam stimulus kemampuan motorik siswa kelas II SDN Karangasem Kulon Progo Yogyakarta - Indriyanti, Poppy; Febriantoro, Rio; Chairiyah, Chairiyah; Nadziroh, Nadziroh (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2024)
Abstract: The aim of this study was to find out the extracurricular role of dance in stimulating motoric ability in grade II students at SD N Karangasem Kulon Progo Yogyakarta. This type of research is descriptive qualitative research. Data collection techniques in this study using: observation, interview, and documentation techniques. The results showed that: (1) The extracurricular role of dance in stimulating the students motoric ability was to help the physical and mental growth and development of students, (2) Motoric ability that can be developed through dance extracurriculars are gross motoric ability and fine motoric ability, (3) Obstacles in dance extracurriculars are: inadequate facilities, differences in gender and physical condition of students, (4) Solutions to overcome obstacles by evaluating and discussing with parents of students, thereby adding synergy with what students must do beyond of implementing dance extracurricular learning so that they can still develop their motoric ability. Keywords: the extracurricular role of dance, stimulus of student motoric ability